Makryna Młodsza, czyli kto? Postać świętej w pismach Grzegorza z Nyssy - Dybała, Jolanta (Przegląd Nauk Historycznych, 2011)
Gregory of Nyssa is the author of his sister, Macrina’s biography. Already as a young girl she decided to lead an ascetic life. The bishop, however, did not describe the fate and experiences of the woman who achieved the ideal of religiousness breaking with the surrounding world and devoting herself entirely to God. The role of a virgin leading a community of nuns was definitely the most important role appointed to Macrina by her brother. In his works, however, especially in the Vita, she was portrayed in a context of the community of virgins as well as her own family. Therefore she was presented as a wife, widow, mother but also a caring daughter and sister. Gregory, casting her in all these roles, added value to Christian marriage, maternity and bringing up children. Macrina’s martyrdom and thaumaturgy were to prove that thanks to her religiousness and grace from God she predominated over other women. The bishop did not hesitate to place her also above outstanding men and he made her their teacher. The way he did it was to convince his readers that she was in fact the author of the teaching about soul and resurrection. Macrina became at the same time the best example of realizing this theological concept. She did not stay indifferent to her relatives’ death, but, on the other hand, she did not allow the sorrow after the loss to rule her mind. Gregory, admiring his sister’s attitude, taught that a Christian should not care about earthly matters. On the other hand, he excluded complete apatheia and showed how meaningful love to the other man was. Gregory’s works concerning Macrina provide his definition of Christian philosophy. It is ascetic life concentrated on prayer and physical work and deep faith that resurrection will restore the original, ideal state which was experienced by man in paradise before the fall. It allows people to exist almost like the angels. Macrina, achieving the highest stage in the development of her spirituality, approached the ideal. Gregory claimed that only her body differentiated her from angels. The bishop claimed that Macrina was better than any of representatives of the female sex, therefore, it was hard to call her a woman. It means that for her brother she became more similar to angels, than to human beings.